Establishment of a thermal process for bagoong alamang (Philippine Shrimp Paste) in bottles - Coorey, Jude Herman Ranil (1991)
A thermal process for bagoong alamang in 12 oz. fancy oval bottles was established. The study involved the characterization of the product based on the heat penetration characteristics, salt content, and water activity. The reference organism was selected based on all factors affecting its growth in the food system. Phase II involved process calculations. Process confirmation by scaling up the process to the pilot scale and subsequent microbiological and sensory evaluation were conducted for phase III. The cold point was found to be at the geometric center of the bottle indicating conduction heating. The pH of the product was 6.7 which classified bagoong alamang to the low acid food category. However, water activity and salt content were found to be 0.82 and 21.3%, respectively. based on these, the reference organism was established. The yeast and molds were identified to be most likely spoilage organisms in the product. However, there is a need to establish a process using a higher margin of safety. Thus, Clostridium botulinum type E was identified as the reference organism. The time-temperature combination established was 15 minutes in a water bath at 212°F. This process gave a lethality value higher than required, calculated lethality was 1.6 to 1.7 minutes against the target F212°F of 0.42 minutes. The 15 minute process was more than adequate to render the product commercially sterile. Microbiological analysis results were negative for the presence of any microorganisms. Finally, sensory evaluation was performed to identify if the process had an adverse effect on the bagoong alamang. Statistical analysis proved that no such effect was noted by the panelist. Hence, a 15 minute process at 212°F for sauteed bagoong alamang in 12 oz. fancy oval bottles was recommended. Further, air cooling the bottles for at least 45 minutes was recommended.